Systematic investigation on parameters of solution blown micro/nanofibers using response surface methodology based on box‐Behnken design. Issue 2 (25th April 2013) - Lou, Huiqing; Li, Wentao; Li, Chulin; Wang, Xinhou
ABSTRACT Response surface methodology, based on the four‐factor, three‐level Box‐Behnken design, has been utilized to facilitate a more systematic understanding of the solution and processing parameters of solution blown polyethylene oxide (PEO) micro/nanofibers. The factors investigated include air pressure, solution concentration, nozzle diameter, and injection rate. Fiber diameters, ranging from 137 to 1982 nm, are associated with these variables by applying a response surface model. The linear coefficients of air pressure and solution concentration, the interactive effect between air pressure and injection rate as well as the quadratic terms of nozzle diameter and injection rate are demonstrated statistically significant. Verification of the response surface model is successfully accomplished. Consequently, this study puts forward an overview of the effect of solution and technical parameters on solution blown submicron PEO fibers and provides a train of thought for fabricating other micro/nanofibers. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1383‐1391, 2013